2002
DOI: 10.1074/jbc.m201504200
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Binds RalA and RalB and Is Required for the Thrombin-induced Activation of Ral in Human Platelets

Abstract: Ral GTPases may be involved in calcium/calmodulinmediated intracellular signaling pathways. RalA and RalB are activated by calcium, and RalA binds calmodulin in vitro. It was examined whether RalA can bind calmodulin in vivo, whether RalB can bind calmodulin, and whether calmodulin is functionally involved in Ral activation. Yeast two-hybrid analyses demonstrated both Rals interact directly but differentially with calmodulin. Coimmunoprecipitation experiments determined that calmodulin and RalB form complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 54 publications
2
34
0
3
Order By: Relevance
“…We and others (29,30,39) have previously shown that Ral is an important partner in calcium and Ca 2ϩ /calmodulin mediated signal transduction pathways. Also, PLC-␦1 is highly sensitive to calcium concentrations and can be activated at concentrations as low as 10 M (40, 41).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We and others (29,30,39) have previously shown that Ral is an important partner in calcium and Ca 2ϩ /calmodulin mediated signal transduction pathways. Also, PLC-␦1 is highly sensitive to calcium concentrations and can be activated at concentrations as low as 10 M (40, 41).…”
Section: Resultsmentioning
confidence: 99%
“…CaM binding assays were performed using 50 l of calmodulinSepharose 4B beads or Sepharose 4B beads blocked with Tris buffer as described previously (30). To confirm the dependence on Ca 2ϩ for CaM binding to PLC-␦1, reactions were performed by incubating purified CaM with GST-PLC-␦1 overnight at 4°C diluted in commercially available Ca 2ϩ calibration buffers (Molecular Probes) exactly as described previously (35).…”
Section: Plasmids and Chemicals-ratmentioning
confidence: 99%
See 3 more Smart Citations